Nowa Konstytucja ZSRR i aktualne problemy rozwoju rad deputowanych ludowych: [New constitution of USSR and current problems concerning the development of the councils of people's deputees] (Studia Prawnicze / The Legal Studies, 1981)
New Constitution of the USSR as well as new constitutions of the union and autonomous republics pointed out a new stage of development of the soviet state, i.e. building of developed socialism and establishing all-national state. Widening of socialist democracy first of all by way of strengthening of position of the councils of people’s deputees is the essence of these changes.Problems concerning the development of the structure of councils which result from amended constitutions may be regarded in three aspects. 1) They illustrate and sum up present stage of development of the councils. 2) They create new possibilities (from the point of view of quality) in the process of management of state and society. 3) They allow the development under the influence of practical experience.Constitutions define the role of the councils and the ties connecting them with other elements of political system. They formulate the principles of democratic centralism, rule of law, openness, constant taking into consideration all the postulates of public opinion and many others.The increase of the constitutional role of the councils influences the change of opinions in science concerning all-national state understood as political unity of the nation on the basis of the developed system of democratic institutions which guarantee exercise of state power by the nation and its participation in management with the aim of realizing the tasks connected with building the communism. According to article 9 of the Constitution of the USSR responsibility for the development of democratic principles and institutions rests on the councils of people’s deputiees.By way of giving over to the councils certain tasks concerning complex development of their territories, new constitutions strengthened the principle of territorial management in the whole system of management of national economy. The realization of democratic rights of the councils depends also upon certain subjective elements which in result causes the necessity of strengthening the ties with the voters. This means participation of the working masses in management of state affairs in particular by way of direct ties of the citizens with the councillors.